Asia-Pacific Regional Integration Index: Construction, interpretation, and comparison - Hyeon-seung Huh; Cyn-young Park (Asian Development Bank (ADB), 2017)
We develop an index to measure the degree of regional integration in Asia and the Pacific (48 economies in six subregions). The index comprises 26 indicators in six dimensions of regional integration, i.e., trade and investment, money and finance, regional value chains, infrastructure and connectivity, free movement of people, and institutional and social integration. We use principal component analysis to apportion a weight to each dimension and indicator to construct composite indexes. The resulting indexes help assess the state of regional integration on diverse socioeconomic dimensions, evaluate progress against goals, identify strengths and weaknesses, and track progress. Cross-country, cross-regional comparisons also allow policy makers to prioritize areas for further efforts.
Keywords: F10; F30; O10; O50; 330; Asia; composite index; regional integration